On Some Formulas for the Index of a Linear Bounded Operator - Khachatryan, Ishkhan (Armenian Journal of Mathematics, 2009)
We consider a linear bounded operator in infnite dimensional separable Hilbert space satisfying some conditions. We prove formulas that can be used to calculate the index of this operator.